The relationship between perceived social support, self-esteem and career decision self-efficacy among first year undergraduate students - Abdullah, Nor Olivia Yan; Roslan, Samsilah (Human Resource Management Academic Research Society, 2021)
Career decision-making is one of the important processes that students, particularly university students, need to emphasise. This study investigates the relationship between three social support dimensions (friends, family, and significant others), self-esteem, and career decision self-efficacy among undergraduates. Cluster random sampling was employed to recruit 190 first-year social science students from a public university in Malaysia. Regression analysis indicated that friend support and self-esteem were positively associated with career decision self-efficacy. The study has also shown that, when it comes to career decision self-efficacy of university students, parental support and support from significant others did not seem to have a significant role. These results can provide information to students, parents, colleges, and career counsellors in the creation of strategies or services that may improve the student's self-efficiency in career decisions.